Wydatki kapituły łęczyckiej na rzecz kolegiaty w świetle not prokuratorów (1406-1419) - Kowalska, Anna (Acta Universitatis Lodziensis. Folia Historica, 2001)
The present article have been written on the basis of the materials preserved in the unpublished manuscripts of the Chapter of Łęczyca. The manuscript preserves acts and receipts of the Chapter, first of all from the first half of the XVth century. The time limits of the paper have been narrowed to the years 1406-1419 because first receipts come from 1406, while the year 1419 is the first year that, after a hectic time, relieved the members of the Chapter from the duty of carrying out renovations and introducing major changes to the church. Procurators’ entries included in the manuscript enable us to research in the expenses of the Chapter in the above-mentioned period. They also allow us to recreate a picture of life around the church. Although preserved entries are not complete; they show that money was spent upon distributions, food, farms, financing trips and the collegiate church. The entries show that the money was spent church renovation and its furnishment, especially that connected with religious services, i.e. church bells, organs, clock, books, wax, incense etc. Consequently, the entries preserve information on craftsmen’s wages, incomes of those who manufactured the bells and the clock, and who profited most from the financial resources of the Chapter. According to the collected data, the record year of expenses on the collegiate was the year 1416 (over 57 marks), while the year 1407 is characteristic of the lowest sum of money spent on the church (under 1 mark). Building materials accounted for the highest sum in the year 1415 (12 marks), while the lowest was recorded in the year 1408 (under 1 mark). Craftsmen working at the collegiate site were paid most in 1416 (over 51 marks), while they took the lowest sum in 1411 (over 2,5 marks). At the same time, in the same year (1411) the highest sum was spent on furnishing the church (over 17 marks), while 8 year later members of the Chapter spent only 1 mark and 4 grosz’es. The sums spent on the up-keeping and furnishing of the church in the above-mentioned seventeen-years period were quite considerable. The total was almost 163,5 marks. Distribution expenses totalled at 208 marks. Another category of expenses (on farm up-keeping) amounted to only 94 marks. Consequently, it is clear that the problem of maintaining and embellishing the collegiate was of importance for the members of the Chapter.